A conductive thin layer on prepared positive electrodes by vapour reaction printing for high-performance lithium-ion batteries. Issue 40 (28th September 2017) - Ahn, Jinhyeok; Yoon, Sukeun; Jung, Seul Gi; Yim, Jin-Heong; Cho, Kuk Young
Abstract : By covering prepared electrodes with a PEDOT layer via VRP, the electrodes exhibited improved electrochemical performance compared to bare electrodes. Abstract : Surface modification, especially by thin-layer coating, has provided a major breakthrough in high-performance lithium-ion batteries (LIBs). Surface coating with conductive materials at the level of single active particles has been used to overcome poor conductivity in electrodes. Nevertheless, the resulting decrease in the volumetric capacity and the complexity of the required manufacturing conditions are problematic for particle-scale coating techniques. Here, we report a facile alternative route to coating conformal thin-layer conducting poly(3, 4-ethylenedioxythiophene) (PEDOT) through vapour reaction printing (VRP) on prepared electrodes. A positive electrode based on micron-sized LiFePO4 (LFP) was used to highlight the possible improvements in the intrinsic limitations of poor electrical and ionic conductivity. The effective conformal surface coating of the thin PEDOT layer was confirmed by scanning electron microscopy and X-ray photoelectron spectroscopy. The PEDOT coated LFP electrodes exhibited outstanding improvements not only in cycling stability, showing 96.6% retention of the initial capacity after 100 cycles, but also in their rate capability, achieving 0.668 mA h at a rate of 1C. The uncoated pristine LFP electrode showed only 23.5% of the initial capacity after 100 cycles and 0.181 mA h at a rate of 1C. These remarkable results were attributed to the conformal PEDOT layer, which offers improved conduction pathways and ion diffusion. Therefore, this new method of coating prepared electrodes with a conductive conformal thin layer is promising for the design of electrodes for high-performance lithium-ion batteries.